PENGEMBANGAN SOAL TERBUKA (OPEN-ENDED PROBLEM) PADA PEMBELAJARAN KOLABORATIF UNTUK MENGUKUR KEMAMPUAN BERFIKIR TINGKAT TINGGI SISWA SMP KELAS VIII - Jannatasari, Nindi Zakia; Trapsilasiswi, Dinawati; Kurniati, Dian (Department of Mathematics Education , University of Jember, 2017)
Abstract. High order thinking skill becomes a goal in the learning activities in Curriculum 2013. High order thinking skill is closely related to how students solve problems in mathematics. To measure students' level of problem solving skills requires an unusual test, which not only contains routine questions and low level questions. One of the mathematics lessons that can familiarize students to use their problem-solving power to measure students' high order thinking in the part of mathematics is the use of open-ended questions. A learning strategy that supports the use of open-ended questions is a collaborative learning strategy. The process of developing open-questions of high-level thinking through 4 stages, namely: (a) preliminary stage (preliminary); (B) the stage of self evaluation (analysis and design); (C) prototyping stage (validation, evaluation and revision); And (d) field test stage. The results of this study indicate that the developed instrument is worthy to be used to measure students' high-order thinking skill. It is based on the validity test with the value of Va generally reach 4.27 with valid interpretation. Reliability test obtained reliability tested in class VIII C and VIII D are 0.7999 and 0.8166 respectively with high interpretation. Based on the difficulty level test obtained the level of difficulty of open questions meet the criteria of a good degree of difficulty. Based on the result of the experiment, it is also known that overall students who have high order thinking skill with good category are 22 students (61,11%) from 36 students in class VIII C and 18 students (51,43%) from 35 students in class VIII D. Key Words: Open Ended Problem, Measuring High Order Thinking Skills, Collaborative Learning